ANALISIS KEKUATAN MENGIKAT KONTRAK SEBAGAI DASAR YURIDIS DALAM BISNIS INTERNASIONAL - Cindawati Cindawati (Arena Hukum, 2016)
AbstractThe purpose of this paper to explain and analyze the binding force of the contract as a legal basis in International business. The method applied is normative, which are based on legal principles contained in the law, or set specific standards or norms against a phenomenon by reviewing secondary data or literature. The result is that a contract or agreement as an expression of the will expressed by the offer and acceptance is regarded as a constitutive element of contractual binding force. Supply and demand contains a promise. The new agreement is formed when there is an encounter or an agreement between the promises devoted to one another. Of the nature and scope of a binding legal contract, there are national contract, a contract made by two individuals in an area of the country that no foreign element. While the international contract is a contract with foreign elements. Â A contract is a legal agreement that can be enforceable, the activities undertaken entrepreneurs. Buy products in one country and sell them in third countries. Firmly binding provision, set the time the contract was agreed upon, signed by both parties. Since starting preparations to transport goods that require funding for preparatory activities up to shipment, payment risks in traveling with the importer. Everything reflects the